2007
DOI: 10.1017/s0950268807008813
|View full text |Cite
|
Sign up to set email alerts
|

A Salmonella Typhimurium 197 outbreak linked to the consumption of lambs' liver in Sydney, NSW

Abstract: We identified an increase in the number of cases of Salmonella Typhimurium phage type 197 in New South Wales in February 2005. Cases were predominantly of Lebanese descent. To identify risk factors for illness, we conducted an unmatched case-control study including 12 cases and 21 controls. Eight of 12 cases (67%) and no controls reported eating lambs' liver (OR incalculable, P<0.05), and seven of nine cases (78%) and one of 21 controls (5%) reported eating fresh fish (OR 70.0, P<0.05). Among participants who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The 2002 outbreak highlighted the need for the daily preparation and storage of raw shell egg-based dressing and dishes under proper conditions at ≤ 5 • C, instead of at room temperature [34]. In another report in 2005, lamb's liver was responsible for an S. Typhimurium outbreak, as shown in Table A1 [36]. Since the majority of S. Typhimurium outbreaks in Australia are associated with the consumption of egg and egg-based foods [19], the identification of lamb's liver as the suspected source of the outbreak was uncommon.…”
Section: New South Walesmentioning
confidence: 99%
“…The 2002 outbreak highlighted the need for the daily preparation and storage of raw shell egg-based dressing and dishes under proper conditions at ≤ 5 • C, instead of at room temperature [34]. In another report in 2005, lamb's liver was responsible for an S. Typhimurium outbreak, as shown in Table A1 [36]. Since the majority of S. Typhimurium outbreaks in Australia are associated with the consumption of egg and egg-based foods [19], the identification of lamb's liver as the suspected source of the outbreak was uncommon.…”
Section: New South Walesmentioning
confidence: 99%
“…Red and white meat, meat products, milk, cheese and eggs are considered the major food sources of human salmonellosis, although a wide variety of other foods have been associated with outbreaks [8]. Other researchers reported that lamb's liver was responsible for an outbreak of S. typhimurium phage-type 197 in Australia [63]. In Germany, from 2001 to 2005, microbiological testing, trace-back investigations and epidemiological studies showed that pork and pork products were involved in human salmonellosis outbreaks [64].…”
Section: Food Of Animal and Plant Origin As A Source Of Salmonella Sementioning
confidence: 99%
“…Examination of slaughter-age healthy sheep and identification of Salmonella species have been often reported in the past few years, due to public health concerns of these serovars entering the human food chain [37]. Ovine salmonellosis might be an important zoonotic reservoir for human infection and a number of studies have reported food-borne transmission to humans [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Salmonella Infections In Sheepmentioning
confidence: 99%